Traumatic Tricuspid Regurgitation Presenting as Refractory Shock After Polytrauma: Diagnostic and Resuscitative Implications - Chiara Angeletti; Giulia Salve; Roberta Maiorino; Franco De Remigis; Davide Pirro; Paolo Di Emidio; Stefano Di Filippantonio; Federica Venturoni (Emergency Care and Medicine, 2026)
In polytrauma patients, persistent or unexplained hemodynamic instability is commonly attributed to hemorrhage, hypovolemia, or septic evolution. Compensatory neuro-cardiovascular responses may temporarily mask structural cardiac injury and delay diagnosis. Traumatic tricuspid valve injury is a rare condition in which physiological compensation and right-ventricular adaptation can initially preserve systemic perfusion but progressively impair circulatory efficiency. We report the case of a young polytrauma patient and a targeted narrative review to shed light on a rare cause of hemodynamic instability in blunt chest trauma, emphasizing that identifying the underlying mechanism of shock is crucial for adequate management.